VD_FINDINFO ML / 2015 / 97 vom 21. Mai 2015 - VD Tribunal cantonal (2015)
PRESCRIPTION, OBLIGATION D'ENTRETIEN, PERSONNE DIVORCÉE, MAINLEVÉE DÉFINITIVE | 128 ch. 2 CO, 130 al. 1 CO, 131 al. 1 CO, 80 al. 1 LP